Perancangan Sistem Informasi Akuntansi Web untuk Agen Properti dengan Metodologi Scrum - Ardiansyah, Muhammad; Phang, Raymond (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to design and develop a web-based accounting information system for real estate agency companies using the Scrum methodology. The system is specifically tailored to address the unique needs of the real estate industry, such as managing sales transactions, calculating agent commissions, client communication, property activity reporting, and structured financial reporting. The Scrum methodology, employed during the development process, offers high flexibility and adaptability, enabling developers to quickly and effectively respond to user feedback. By utilizing technologies like PHP, MySQL, HTML, and CSS, the system development process is accelerated, structured, and maintainable. The system is designed to enhance efficiency, transparency, and accuracy in managing property transaction data, enabling management to access real-time activity reports, effectively organize properties, and transparently evaluate sales transactions. The results demonstrate that the system significantly improves the productivity of real estate companies, enhances financial reporting transparency, and supports better data-driven decision-making. Through this system, business processes become more integrated, fostering more productive team collaboration and increasing the company's competitiveness within the real estate industry. Additionally, the system includes an audit trail feature that ensures data accuracy and simplifies both internal and external audit processes. This adds value by building trust among users, including internal management and external stakeholders such as investors or regulators. By combining modern technologies and the Scrum methodology, this study aims to serve as a significant reference for similar system development initiatives within the real estate sector and beyond.